Welcome to the "Treaty Claims - The Unfinished Business" Conference - Durie, E T (Victoria University of Wellington Law Review, 1995)
Chief Judge Durie of the Māori Land Court welcomes the attendees of the "Treaty Claims: The Unfinished Business" Conference from the Institute of Advanced Legal Studies.